ВИВЧЕННЯ ТЕПЛОПРОВІДНОСТІ WC-Co ТВЕРДИХ СПЛАВІВ ОБРОБЛЕНИХ ТИСКОМ 8 ГПа ЗА ВИСОКОЇ ТЕМПЕРАТУРИ - Гнатенко, Ірина; Бєляєв, Антон; Андреєв, Ігор; Осіпов, Олександр (Институт сверхтвердых материалов им. В. Н. Бакуля Национальной академии наук Украины, 2024)
Sintered cemented carbides are the most common type of material used in cutting tools due to their good combination of high hardness and strength. High temperatures generated during processing can have a harmful effect on the cutting tool. Thus, the ability of a tool material to efficiently dissipate heat (the thermal conductivity) is an important property to understand and quantify. There is not enough information on the influence of various technological techniques, such as mechanical, thermomechanical, thermal and barothermal processing on the thermal conductivity of cemented carbides in the literature. Therefore, the thermal conductivity of sintered cemented carbides types of WC-6Co and WC-15Co was studied in this work as a result of the effect on them of high pressure of 8 GPa and high temperature (HPНT treatment). To measure the coefficient of thermal conductivity, the standard method was used, which was implemented with the help of a computerized installation developed at the Institute of Superhard Materials named after V.M. Bakulya of the National Academy of Sciences of Ukraine. The research was carried out on samples made of hard alloys WC-6Co and WC-15Co sintered and processed in high-pressure apparatus of the "Toroid" type. The results show that the thermal conductivity is significantly affected by the Co content, WC grain size, and mode of subsequent HPНT processing. The thermal conductivity of WC-15Co sintered hard alloys is 110 W/m·K, and WC-6Co hard alloy is 124 W/m·K . It was established that the application of HPНT treatment to sintered hard alloys leads to a decrease in their thermal conductivity. The paper also shows the effectiveness of the application of the presented method, which allows evaluating changes in thermal conductivity within one brand of alloy as a result of their additional HPНT processing.